Breeze / Afiq Hijizi Mohamad Saparie ... [et al.] - Mohamad Saparie, Afiq Hijizi; Awg Iberahim, Muhammad Fadhil; Junaidi, Siti Najiha; Jamel, Nur Shuhadah; Awang Omar, Awang Adzli (2016)
Detergent is a simply defined as a cleaning agent in a dictionary. As we known many of company have distributes detergent in the market nowadays. One of the detergents in the market is a Breeze. Breeze is a laundry product, Breeze has a complete range of laundry products with great cleaning power of all your laundry needs. Breeze laundry detergent will suit washing needs. Breeze also have one tagline it is that dirt is good, it might sound unusual for a leading laundry brand, but there's a good reason for our philosophy. Breeze believes that children should feel free to explore, learn and develop also sometimes getting a few stains along the way is part of the process. Breeze is dedicated to showing you that dirt isn't always bad. In fact, Dirt is Good especially when it's the result of your kids going out into the world to have fun, explore, learn and experience the very best the world around us has to offer. Not only will this help develop kids' understanding of their world, the environment and nature, it will also shape their values, grow their confidence, benefit their health and ultimately help them reach important milestones.